Blocking the Initiation of Coagulation by RNA Aptamers to Factor VIIa - Rusconi, Christopher P.; Yeh, Alice; Lyerly, H. Kim; Lawson, Jeffrey H.; Sullenger, Bruce A. (Thrombosis and Haemostasis, 2000)
The tissue factor/factor VIIa complex is thought to be the primary initiator of most physiologic blood coagulation events. Because of its proximal role in this process, we sought to generate new inhibitors of tissue factor/factor VIIa activity by targeting factor VIIa. We employed a combinatorial RNA library and in vitro selection methods to isolate a high affinity, nuclease-resistant RNA ligand that binds specifically to coagulation factor VII/VIIa. This RNA inhibits the tissue factordependent activation of factor X by factor VIIa. Kinetic analyses of the mechanism of action of this RNA suggest that it antagonizes factor VIIa activity by preventing formation of a functional factor VII/tissue factor complex. Furthermore, this RNA significantly prolongs the prothrombin time of human plasma in a dose dependent manner, and has an in vitro half-life of ∼15 h in human plasma. Thus, this RNA ligand represents a novel class of anticoagulant agents directed against factor VIIa.
Keywords: Factor VIIa; aptamer; FVIIa inhibitors; in vitro selection; thrombosis